2015
DOI: 10.1111/epi.12957
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in epilepsy for the Asia‐Oceanian region

Abstract: SUMMARYThe Asia-Oceanian region is the most populous region in the world. Although there has been substantial economic development and improvement in health services in recent years, epilepsy remains generally an underrecognized and understudied condition. To help promote research in the region, the Commission on Asian and Oceanian Affairs (CAOA) of the International League Against Epilepsy (ILAE) appointed the Research Task Force (RTF) to facilitate the development of research priorities for the region.Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Standardized epidemiologic and surveillance studies are needed to provide more widespread accurate data. The Research Task Force of the Commission on Asian and Oceanian Affairs of the International League Against Epilepsy has developed research priorities for the region, including studies to increase knowledge of the burden of epilepsy in the region, with the aim of improving access to care and reducing the treatment gap; to improve understanding of the causes and risk factors of epilepsy, including pathologic, genetic, and lifestyle factors; to alleviate the consequences of epilepsy by reducing stigma and discrimination and improving QOL; to develop improved therapies and treatment delivery to improve therapeutic outcomes; and to improve the research infrastructure and capacity …”
Section: The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Standardized epidemiologic and surveillance studies are needed to provide more widespread accurate data. The Research Task Force of the Commission on Asian and Oceanian Affairs of the International League Against Epilepsy has developed research priorities for the region, including studies to increase knowledge of the burden of epilepsy in the region, with the aim of improving access to care and reducing the treatment gap; to improve understanding of the causes and risk factors of epilepsy, including pathologic, genetic, and lifestyle factors; to alleviate the consequences of epilepsy by reducing stigma and discrimination and improving QOL; to develop improved therapies and treatment delivery to improve therapeutic outcomes; and to improve the research infrastructure and capacity …”
Section: The Futurementioning
confidence: 99%
“…The Research Task Force of the Commission on Asian and Oceanian Affairs of the International League Against Epilepsy has developed research priorities for the region, including studies to increase knowledge of the burden of epilepsy in the region, with the aim of improving access to care and reducing the treatment gap; to improve understanding of the causes and risk factors of epilepsy, including pathologic, genetic, and lifestyle factors; to alleviate the consequences of epilepsy by reducing stigma and discrimination and improving QOL; to develop improved therapies and treatment delivery to improve therapeutic outcomes; and to improve the research infrastructure and capacity. 131 In 2015, the WHO passed the Epilepsy Resolution (EB136.R8) to promote coordinated action against the treatment gap, which may provide an important opportunity to prioritize epilepsy in Asia. 95 Evidence-based epilepsy care guidelines have been developed for use in low-and middle-income countries.…”
Section: The Futurementioning
confidence: 99%
“…apathy [8], altered self-identity, memory loss) [9], and marital and family problems [10]. The 2015 International League Against Epilepsy Asia-Oceania Research Task Force has highlighted the need to alleviate the psychosocial consequences of epilepsy as a research priority [11]. Epilepsy can have a https://doi.org/10.1016/j.clineuro.2019.02.022 Received 13 January 2019; Received in revised form 12 February 2019; Accepted 25 February 2019 critical impact of a person's life [12], with early frequent emotional problems and neuropsychological deficits [12][13][14], and ongoing financial burden [15], which can affect adjustment and patterns of disability.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do this, Chi-Wan (2007) and Lim and Pan (2005) suggested that a uniform study protocol can be designed to collect data on "public awareness, understanding and attitudes toward epilepsy" and "patients" perception of having epilepsy" and followed by conducting survey among the general population, patients with epilepsy, family members, health providers, or school teachers. A Research Task Force (RTF) was formed by the Commission on Asian and Oceanian Affairs (CAOA) of the International League Against Epilepsy (ILAE) to promote research in epilepsy in Asia-Oceanian region with the ultimate aim to improve the lives of PWE (Kwan et al 2015).…”
Section: The Future Of Research In Neuropsychology Of Epilepsy In Malmentioning
confidence: 99%